The Relationship Between Parental Education Level and Parenting Patterns on the Incidence of Stunting Among Children Aged 6–24 Months - Setyadi, Muhammad Rofi Wahyu; Nurbaiti, Lina; Paramaiswari, Nurul Firdausi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A public health concern, stunting impacts children's physical and cognitive development, especially in toddlers. In order to prevent stunting, socioeconomic factors including parental education and parenting style are crucial. The purpose of this study was to examine the relationship between stunting in children aged 6 to 24 months in the Puyung Public Health Center's service area in Central Lombok and parental education and parenting style. This observational study used a cross-sectional design involving eight integrated health posts (posyandu). Stratified random sampling was used to identify 90 parents with children between the ages of 6 and 24 months as study participants. Information was gathered via questionnaires and the Maternal and Child Health (MCH) book. The chi-square test was used for bivariate analysis. 54.4% of the population was stunted. The majority of dads (48.9%) and women (46.7%) had completed senior high school. The majority of respondents (73.3%) thought that parenting was good, with democratic parenting being the most popular (46.7%). There was no statistically significant correlation between the incidence of stunting (p>0.05) and maternal education (p=0.080), father education (p=0.387), parenting category (p=0.655), or parenting type (p=0.402). In conclusion, there was no discernible link between stunting in children aged 6 to 24 months in the Puyung Public Health Center's service area in Central Lombok and parental education or parenting style. More studies with bigger sample sizes and examination of other affecting variables like socioeconomic status and diet are among the recommendations.